Governance, Ethics and Public Service Delivery: The Ramifications of Corruption - Malesela Jim Masenya; Admire Mthombeni (Center for Risk Management & Sustainability and RSF Press, 2023)
The purpose of this paper is to illustrate the repercussions of corrupt practices in the South African public sector and to recognise the critical need for ethical control to promote good governance. Since the advent of democracy in 1994, there has been a myriad of incidents of corruption involving public servants in South Africa. Corruption is now recognised as one of the South African government's greatest challenges, with numerous consequences for public service delivery in that the resources that are meant to assist the poor are diverted to benefit a few corrupt officials. Corruption undermines democracy and social justice, thus deepening poverty, increasing organised crime and stunting efforts to stimulate human security. The incidents of corruption characterised by colossal theft, embezzlements and rampant bribery are the basis of knowledge around the ability of the government to deal effectively with dishonesty. The paper will use a literature review to argue and demonstrate that despite the devotion of the government to combat unethical conduct of public servants by formulating various pieces of legislation and policies as an attempt to address the problem of unethical behaviour, the tribulations of corruption and problems of immoral conduct by public servants continue to escalate, thus, perpetuating poor provision of public service. The paper concludes that continued unethical practices by public servants cannot go unpunished; ethics must be enforced to enhance public service delivery.